2017
DOI: 10.1097/md.0000000000006459
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of better outcomes by monotherapy of an antivascular endothelial growth factor drug, ranibizumab, for diabetic macular edema in clinical practice

Abstract: Intravitreal ranibizumab (IVR) has been approved for treating diabetic macular edema (DME), and is used in daily clinical practice. However, the treatment efficacies of IVR monotherapy in real-world clinical settings are not well known.The medical records of 56 eyes from 38 patients who received their first IVR for DME between April 2014 and March 2015, and were retreated with IVR monotherapy as needed with no rescue treatment, such as laser photocoagulation, were retrospectively reviewed. The clinical course,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 31 publications
(40 reference statements)
1
39
2
Order By: Relevance
“…Campochiaro et al [36] found that DME patients with better BCVA at the baseline improved better after IVR treatment compared with those with worse BCVA at the baseline. Ozawa et al [37] also reported similar results, suggesting that an early IVR treatment may be more efficient in DME patients. However, in the present study, an association between CRT values at the baseline and BCVA or CRT at 24 weeks has not been confirmed.…”
Section: Discussionmentioning
confidence: 62%
“…Campochiaro et al [36] found that DME patients with better BCVA at the baseline improved better after IVR treatment compared with those with worse BCVA at the baseline. Ozawa et al [37] also reported similar results, suggesting that an early IVR treatment may be more efficient in DME patients. However, in the present study, an association between CRT values at the baseline and BCVA or CRT at 24 weeks has not been confirmed.…”
Section: Discussionmentioning
confidence: 62%
“…A recent study has also reported that patients with poorer baseline best‐corrected visual acuity (BCVA) experienced greater improvement in BCVA than patients with higher baseline BCVA, but better clinical outcome values can be achieved with early treatment (i.e. before BCVA and central retinal thickness deteriorate) . Additionally, suboptimal early BCVA response to DME treatment has been reported to be an indicator for poorer long‐term visual outcomes than eyes that have a pronounced early response .…”
Section: Introductionmentioning
confidence: 99%
“…before BCVA and central retinal thickness deteriorate). 20 Additionally, suboptimal early BCVA response to DME treatment has been reported to be an indicator for poorer long-term visual outcomes than eyes that have a pronounced early response. 21 Currently, aflibercept, bevacizumab and ranibizumab are the three anti-VEGF treatments often used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the real-life clinical setting, intensive regimen protocols are not possible to be implemented, due to the excessive personal and financial burden on the patients and institutions still associated with approved anti-VEGF medication. In fact, the true outcome of anti-VEGF agents in DME and their practical benefits in regular clinical practice have not been studied very well, and undertreatment is a major risk factor for patients [4, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Individuals can be affected by DME in their working years, and the chronic nature of the disease is associated with high costs related to visual disability and treatment burden. These are expected to increase as the global prevalence of diabetes also increases [2-4]. …”
Section: Introductionmentioning
confidence: 99%